Legal analysis of the application of ultimum remedium towards state officials' discretion causing state financial losses - Sianturi, Ronald Hasudungan (Priviet Social Sciences Journal, 2025)
This study aims to analyze the application of the ultimum remedium principle to discretionary actions by state officials that result in financial losses to the state. In practice, the law enforcement of discretionary actions often gives rise to debates between protecting the freedom of administrative decision-making and enforcing criminal law within the framework of corruption eradication. This study uses a normative legal method with a statute, conceptual, and case study approach, which allows for a comprehensive analysis of the applicable legal framework and its implementation practices. The results show that the application of the ultimum remedium principle is in line with the principle of due process of law and the protection of legitimate discretion, as long as it meets the elements of compliance with procedures, is based on good faith, and is not motivated by self-enrichment or other motives. Thus, criminal law is truly applied as a means of last resort, achieving a balance between protecting public officials with integrity and effective law enforcement to realize good governance, where policy innovation and courage to make decisions are protected, without neglecting accountability and integrity in government administration.